2018
DOI: 10.1016/j.jaci.2017.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation predisposes allergic mice to neutrophilic lung inflammation

Abstract: Collectively, our data show that sleep quality participates in the progression of allergen-induced eosinophilic lung inflammation to corticosteroid-refractory neutrophilic manifestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Diverse mechanisms may be presumed for sleep deprivation to affect the exacerbation of allergic reactions. As is well known, sleep deprivation is associated with chronic inflammation, nervous or hormonal imbalance, and immunologic change [8,9,11,12]. These can cause or worsen allergic responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diverse mechanisms may be presumed for sleep deprivation to affect the exacerbation of allergic reactions. As is well known, sleep deprivation is associated with chronic inflammation, nervous or hormonal imbalance, and immunologic change [8,9,11,12]. These can cause or worsen allergic responses.…”
Section: Discussionmentioning
confidence: 99%
“…They found that REM sleep is related to nocturnal asthma, probably because of changes in sympathetic modulation. Nunes et al [9] examined the effect of sleep deprivation on allergen-induced airway inflammation in an ovalbumin (OVA)-sensitized mice model and reported that there were severe lung inflammation in the sleepdeprived OVA-sensitized mice group compared to the control group. In detail, their results indicated that sleep deprivation is related to elevated IL-17 levels, pulmonary neutrophilia, and resistance to corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep deprivation was performed using a modi ed multiple platform method [24,25]. Mice were placed in a ventilated transparent cage (50 × 30 × 17cm; 3 mice/cage) containing 9 circular platform (3.5cm in diameter) surrounded by water up to 1cm beneath the upper surface of the platforms enabling the mice to move between the platforms.…”
Section: Sleep Deprivation Modelmentioning
confidence: 99%
“…We know that during sleep there is production of pro-and anti-inflammatory cytokines, however, production of inflammatory cytokines is observed in sleep deprivation. In the experimental study by Nunes et al [2], it was possible to demonstrate that mice in sleep deprivation had more inflammatory cytokines than those allowed for good quality sleep. In addition, mice in sleep deprivation after corticotherapy (dexamethasone) were not able to reduce production of IL-17 and TNFalpha in the same way as mice that had good quality of sleep.…”
mentioning
confidence: 99%